Migrant Health Country Profile tool (MHCP-t) for transforming health data collection and surveillance in the Middle East and North African (MENA) region: tool development protocol with embedded process evaluation - Farah Seedat; Bouchra Assarag; Kolitha Wickramage; Sally Hargreaves; Ana Requena-Mendez; Dominik Zenner; Anna Deal; Stella Evangelidou; Oumnia Bouaddi; Moudrick Abdellatifi; Hassan Edries; Eman Elafef; et al. (BMJ Open)
Introduction The Middle East and North Africa (MENA) region is characterised by major health disparities and complex migration flows. Yet, because of a lack of epidemiological data, there is an urgent need to strengthen routine data collection around migrant health and to define key indicators towards migrant health monitoring. To address this problem, we aim to design and pilot test the Migrant Health Country Profile tool (MHCP-t) which can collate country-level data collection around migration health data, policies and healthcare provision.Methods and analysis The MHCP-t development is a stepwise process that will integrate a process evaluation model with active involvement and engagement of multilevel stakeholders. First, towards the generation of indicators, qualitative field activities will be conducted in different regions in Morocco, Tunisia and Egypt with migrants (n=50 per region), migrant community leaders (n=20 per region) and professionals working with them (n=20 per region). Deductive–inductive thematic analysis will be applied to the data collected. Results from the national qualitative studies and a series of systematic reviews in the MENA region will conclude with a first draft of tool indicators which will be reviewed by national and international experts using the Nominal Group Technique. The revised indicators will be entered into an electronic data capture system and the tool will be pilot-tested by applying a mixed-methods process evaluation to examine its relevance, comprehensiveness, comprehensibility and other practical issues, such as completion time and ease of responding. Mechanisms of change will be assessed on how the participative interactions towards the tool development can trigger change at national and regional levels.Ethics and dissemination The study protocol has been approved by the institutional review boards at the Hospital Clinic in Barcelona, Spain, the University of Sousse in Sousse, Tunisia, the University Hospital of Tanger, Morocco and Badr University of Cairo in Egypt. Findings will be disseminated in peer-reviewed journals and communications to national and regional congresses.